2021
DOI: 10.3389/fphys.2021.583370
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Arterial Elastance Is Associated With the Vascular Waterfall in Patients Treated With Norepinephrine: An Observational Study

Abstract: Introduction: It has been suggested that dynamic arterial elastance (Eadyn) can predict decreases in arterial pressure in response to changing norepinephrine levels. The objective of this study was to determine whether Eadyn is correlated with determinants of the vascular waterfall [critical closing pressure (CCP) and systemic arterial resistance (SARi)] in patients treated with norepinephrine.Materials and Methods: Patients treated with norepinephrine for vasoplegia following cardiac surgery were studied. Vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Consequently, by explaining the pressure gradient between arteriolar closure pressure Pcc and the mean venous filling pressure Pmsf at the level of small veins, vascular waterfall phenomenon is an important discovery in the study of the microcirculation system, and with the further research of many scholars this phenomenon can be measured stably and reliably. In recent years, more and more studies have been conducted to explore and explain related circulation problems by measuring vascular waterfall, which is an important bridge between the study of macrocirculation and microcirculation [ 15 ]. Therefore, in this paper, the hemodynamic response to esmolol in septic shock patients was studied utilizing bedside measurement of Pcc and Pmsf.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, by explaining the pressure gradient between arteriolar closure pressure Pcc and the mean venous filling pressure Pmsf at the level of small veins, vascular waterfall phenomenon is an important discovery in the study of the microcirculation system, and with the further research of many scholars this phenomenon can be measured stably and reliably. In recent years, more and more studies have been conducted to explore and explain related circulation problems by measuring vascular waterfall, which is an important bridge between the study of macrocirculation and microcirculation [ 15 ]. Therefore, in this paper, the hemodynamic response to esmolol in septic shock patients was studied utilizing bedside measurement of Pcc and Pmsf.…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms using the monitoring dynamic arterial elastance were proposed in ICU and they demonstrated that early weaning of norepinephrine may be associated with better tissue perfusion (12,35). As the dynamic arterial elastance was shown to be correlated with V-A coupling and microcirculation (36,37), the connection with VO 2 in our study might contribute with a new puzzle piece. One advantage of V-A coupling is that it can be non-invasively measured at bedside.…”
Section: Clinical Relevance Of V-a Coupling In Icu Patientsmentioning
confidence: 53%
“…Of note, compared with the usual care, the improvement of VAC in the VAC-optimized group was primarily caused by a decreased Ea value that resulted from a slightly lower infused dose of NE. It has been demonstrated that NE has extensive effects on the resistive (i.e., total peripheral resistance) and pulsatile component (i.e., arterial compliance) of arterial load and thus alters arterial elastance [18,28,29]. Therefore, increased arterial load by a high dose of NE could lead to ventricular-arterial uncoupling.…”
Section: Discussionmentioning
confidence: 99%